Effects of physiotherapy on balance and unilateral vestibular hypofunction in vertiginous elderly - Rocha Júnior, Paulo Roberto; Da Silva Peres, Amanda; Garbi, Fernando Pereira; Frizzo, Ana C.F. [UNESP]; Valenti, Vitor E. [UNESP] (Springer Nature, 2014)
Background: We aimed to analyze the effect of a physical therapy protocol on unilateral vestibular hypofunction and overall balance in elderly with vertigo. Methods. The study included nine subjects, four male subjects (68.5 ± 11.09 years old) and five females (72.4 ± 7.09 years old). It was used the performance-oriented Mobility Assessment (POMA), to evaluate the balance and the Unterberger - Fukuda test for analysis of unilateral vestibular dysfunction through rotations and displacements of the body. We developed and applied a structured physical therapy protocol, consisting of group exercises. Results: It was observed that after the protocol, all participants improved balance (33.9 ± 5.1 vs. 47.3 ± 7.6, p < 0.0001) and displacement (111.1 ± 38.0 vs. 53.3 ± 34.6, p = 0.0001). However, it was not found significant differences for rotation. Conclusion: The proposed protocol has contributed to an improvement in balance and vestibular dysfunction of the aged. © 2014 Rocha Júnior et al.; licensee BioMed Central Ltd.
Keywords: Aged; Physical therapy modalities; Postural balance; Vestibular diseases